Analysis and Optimization of p-Xylene Production Process - Ashraf, Muhammad Tahir (2013)
A Master of Science thesis in Chemical Engineering by Muhammad Tahir Ashraf entitled, "Analysis and Optimization of p-Xylene Production Process," submitted in June 2013. Thesis advisor is Dr. Rached Mohamed Chebbi and Co-advisor is Dr. Naif Abdelaziz Darwish. Available are both soft and hard copies of the thesis.